Upper arm fat and muscle in stunted and non-stunted children aged 0-24 months - Bagus Winandi Arundito; Madarina Julia; Neti Nurani; Endy Paryanto Prawirohartono (Indonesian Pediatric Society, 2017)
Background The prevalence of stunting in Indonesia is high, with particularly negative impacts on health during childhood as well as adolescence. Stunting impacts the health of children as well as adults, especially withÂ regards to future obesity. Therefore, evaluating body composition of stunted children before 2 years of age is necessary.Objective To compare upper arm fat and muscle measurements in stunted and non-stunted children aged 0-24 months of age.Methods We analyzed secondary data of the Division of Nutrition and Metabolic Disease, Department of Child Health, Universitas Gadjah Mada Medical School, Yogyakarta which were collected using cluster random sampling from the Yogyakarta Special Province. We compared upper arm fat area (UFA), including the upper arm fat area estimate (UFE) and the upper arm fat percentage (UFP), as well as upper arm muscle area (UMA) and upper arm muscle area estimate (UME), among stunted and non-stunted children aged 0-24 months.Results We analyzed 2,195 children. The prevalence of stunting was 354/2,195 (16.1%). The UFA, UFE, and UFP among stunted children were significantly lower compared to non-stunted children aged 7-12 months [UFA: 4.48 vs. 5.05 cm2 (P <0.001), respectively; UFE: 4.88 vs. 5.55 cm2 (P <0.001), respectively; and UFP: 30.82 vs. 32.58% (P = 0.03), respectively]. The UMA in children aged 7-12 months was also significantly lower in stunted than in non-stunted children [11.31 vs. 11.79 cm2 (P = 0.02), respectively], as well as in children aged 13-24 months [11.05 vs. 11.75 cm2 (P <0.001), respectively]. In addition, the UME in children aged 13-24 months was significantly lower in stunted compared to non-stunted children [10.50 vs. 11.18 cm2 (P <0.001), respectively].Conclusion The UFA in children aged 7-12 months is smaller in stunted than in non-stunted children, whereas UMA in children aged 7-12 months and 13-24 months was smaller in stunted compared to non-stunted children.